Post‐translational methylations of the archaeal Mre11:Rad50 complex throughout the DNA damage response. Issue 2 (19th February 2016) - Kish, Adrienne; Gaillard, Jean‐Charles; Armengaud, Jean; Elie, Christiane
Summary: The Mre11:Rad50 complex is central to DNA double strand break repair in the Archaea and Eukarya, and acts through mechanical and nuclease activities regulated by conformational changes induced by ATP binding and hydrolysis. Despite the widespread use of Mre11 and Rad50 from hyperthermophilic archaea for structural studies, little is known in the regulation of these proteins in the Archaea. Using purification and mass spectrometry approaches allowing nearly full sequence coverage of both proteins from the species Sulfolobus acidocaldarius, we show for the first time post‐translational methylation of the archaeal Mre11:Rad50 complex. Under basal growth conditions, extensive lysine methylations were identified in Mre11 and Rad50 dynamic domains, as well as methylation of a few aspartates and glutamates, including a key Mre11 aspartate involved in nuclease activity. Upon γ‐irradiation induced DNA damage, additional methylated residues were identified in Rad50, notably methylation of Walker B aspartate and glutamate residues involved in ATP hydrolysis. These findings strongly suggest a key role for post‐translational methylation in the regulation of the archaeal Mre11:Rad50 complex and in the DNA damage response. Abstract : The key DNA repair Mre11:Rad50 (MR) complex acts through conformational changes induced by ATP binding/hydrolysis. We show that in the archaeon Sulfolobus acidocaldarius, domains central to MR structure/activities are extensively methylated on Lys and a few Asp/Glu, and that DNA damage induces additional methylations of key Rad50 residues, including Walker B Asp/Glu involved in ATP hydrolysis. This supports a role for archaeal post‐translational methylations in the MR complex regulation and in the DNA damage response.